Examination of 131I and 137Cs releases during late phase of Fukushima Daiichi NPP accident by using 131I/137Cs ratio of source terms evaluated reversely by WSPEEDI code with environmental monitoring data. Issue 8 (3rd August 2017) - Hidaka, Akihide; Yokoyama, Hiroya
ABSTRACT: To investigate what happened in reality during the Fukushima Daiichi Nuclear Power Plant accident, the phenomena within reactor pressure vessel and the discussion of ties with the environmental monitoring measurement are very important. However, the previous study that treats phenomena of the both has not necessarily advanced up to the present time. The source terms predicted by simulation codes such as MELCOR has not yet been consistent with the reverse estimation by WSPEEDI code using environmental measurement data. This study investigated 131 I and 137 Cs release behaviors during the late phase of the accident to contribute to such examination using the 131 I/ 137 Cs ratio of the new source terms predicted by Katata. The 131 I release by the gas–liquid partition from the contaminated water in the 1F2 and 1F3 reactor buildings which was pointed out in the previous study was reevaluated using the new source terms. In addition, paying attention to the similarity of the core conditions between the Fukushima accident and the Phébus FPT3 experiment using the B4 C control rods, the release of organic iodine (CH3 I) during the 1F3 suppression pool venting, formation of CsBO2 and its release behavior were examined which have not yet been sufficiently studied so far.